Envelhecimento ativo e educação: Universidade Sênior de Bagé - Gomes, Daiane Madeira (2017)
The present work is a construction of knowledge carried out through scientific research, which investigates non - formal education for the elderly, whose purpose is the conclusion of the Specialization Course on Education and Cultural Diversity of the Federal University of Pampa (Unipampa). This monograph had as objective to obtain a more detailed knowledge about the Senior University of Bagé and also about the active aging of the students of the same, besides verifying the curriculum developed, analyzing the psychosocial and cultural changes of the elderly. As a methodological process, an exploratory research with a qualitative design was used. For this, interviews were conducted with the coordinator in force in 2016, and soon after with some students of the institution who agreed to participate voluntarily. From the analysis of these data, the following categories were listed: The Beginning of Everything, Elderly in Constant Movement, Physical and Psychological Well-Being, Obstacles in the Course and Power of Life. The paper describes the implementation of the Senior University in the Elderly Center, the construction of the curriculum according to non-formal education also linked to the benefits for active aging. Finally, it is concluded that the Senior University of Bagé is directly linked to the psychosocial, cultural and health changes of the elderly, providing an active aging.